A Sustainable Method for Removal of the Full Range of Liquid and Solid Hydrocarbons from Water Including Up- and Recycling - Gaß, Henrik; Sarcletti, Marco; Müller, Lukas; Hübner, Sabine; Yokosawa, Tadahiro; Park, Hyoungwon; Przybilla, Thomas; Spiecker, Erdmann; Halik, Marcus (Advanced Science, 2023)
Beyond their CO2 emittance when burned as fuels, hydrocarbons (HCs) serve as omnipresent raw materials and commodities. No matter if as liquid oil spills or the endless amounts of plastic roaming the oceans, HCs behave as persistent pollutants with water as main carrier to distribute. Even if their general chemical structure [-(CH2)n-] is quite simple, the endless range of n leads to contaminations of different appearances and properties. A water remediation method based on superparamagnetic iron oxide nanoparticles (SPIONs) modified with self-assembled monolayers of alkyl phosphonic acid derivatives is presented. These molecules enable the SPIONs to non-covalently bind HCs, independently from the molecular weight, size and morphology. The attractive interaction is mainly based on hydrophobic and Coulomb interaction, which allows recycling of the SPIONs. The superparamagnetic core allows a simple magnetic collection and separation from the water phase which makes it a promising addition to wastewater treatment. Agglomerates of collected plastic “waste” even exhibit superior adsorption properties for crude oil, another hydrocarbon waste which gives these collected wastes a second life. This upcycling approach combined with presented recycling methods enables a complete recycling loop.<br

Magnetic Removal of Micro- and Nanoplastics from Water—from 100 nm to 100 µm Debris Size - Gaß, Henrik; Höfling, Anna; Müller, Lukas; Rockmann, Linda; Schubert, Dirk W.; Halik, Marcus; Kloos, Tonya (Small, 2023)
Clean water is one of the most important resources of the planet but human-made contamination with diverse pollutants increases continuously. Microplastics (<5 mm diameter) which can have severe impacts on the environment, are present worldwide. Degradation processes lead to nanoplastics (<1 µm), which are potentially even more dangerous due to their increased bioavailability. State-of-the-art wastewater treatment plants show a deficit in effectively eliminating micro- and nanoplastics (MNP) from water, particularly in the case of nanoplastics. In this work, the magnetic removal of three different MNP types across three orders of magnitude in size (100 nm–100 µm) is investigated systematically. Superparamagnetic iron oxide nanoparticles (SPIONs) tend to attract oppositely charged MNPs and form aggregates that can be easily collected by a magnet. It shows that especially the smallest fractions (100–300 nm) can be separated in ordinary high numbers (1013 mg−1 SPION) while the highest mass is removed for MNP between 2.5 and 5 µm. The universal trend for all three types of MNP can be fitted with a derived model, which can make predictions for optimizing SPIONs for specific size ranges in the futur

Magnetic Resonance Imaging-Based Monitoring of the Accumulation of Polyethylene Terephthalate Nanoplastics - Bashirova, Narmin; Butenschön, Erik; Poppitz, David; Gaß, Henrik; Halik, Marcus; Dentel, Doreen; Tegenkamp, Christoph; Matysik, Joerg; Alia, A. (Molecules, 2024)
Polyethylene terephthalate (PET) is one of the most produced plastic materials in the world. The emergence of microplastics and nanoplastics (MPs/NPs) as a significant environmental contaminant has become a matter of increasing concern. While the toxicological effects of PET NPs have been widely researched, there is a lack of methodologies for studying their accumulation. The present study introduces a novel method to monitor the distribution of PET NPs in germinating wheat (Triticum aestivum L.) seeds. This involves the functionalization of superparamagnetic iron oxide nanoparticles (SPIONs) with PET NPs (PET–fSPIONs) coupled with magnetic resonance microimaging (µMRI) to provide insight into their distribution within the seed. The present study has demonstrated that PET–fSPIONs accumulate in specific regions of germinating wheat seeds, including the shoot apical meristem, the radicle, the coleoptile, the plumule, and the scutellum. Furthermore, the accumulation of PET–fSPIONs has been shown to exert a discernible effect on spin–spin relaxation (T2), as observed via MRI and quantitative T2 relaxation time analysis. The accumulation of PET NPs in embryo regions was also confirmed by SEM. Diffusion-weighted magnetic resonance imaging (DW-MRI) and non-invasive chemical shift imaging analyses demonstrated that PET NPs resulted in restricted diffusion within the highlighted areas, as well as an impact on lipid content. Our study reveals that using µMRI with fSPIONs provides a non-invasive method to monitor the biodistribution of PET nanoparticles in wheat seeds. Additionally, it offers valuable insights into the microstructural interactions of PET.
CRIS-Team Scopus Importer:2024-10-04
Keywords: nanoplastics; polyethylene terephthalate; SPION; wheat; µMRI

Real-time monitoring of magnetic nanoparticle-assisted nanoplastic agglomeration and separation from water - Groppe, Philipp; Wintzheimer, Susanne; Eigen, Andreas; Gaß, Henrik; Halik, Marcus; Mandel, Karl (Environmental Science: Nano, 2022)
Nanoplastics are one of the main modern concerns in water pollution and are suspected to have severe negative impacts on their surrounding ecosystems. The use of superparamagnetic iron oxide nanoparticles (SPIONs) as remediation agents is a suggested approach to address this issue. Their nanoparticulate and switchable magnetic properties enable a homogeneous distribution while magnetic collectability is feasible. However, uncertainties regarding an incomplete collection from treated water remain, which would pose another environmental burden. Herein, the nanoplastic remediation approach via SPIONs is investigated by utilizing magnetic particle spectroscopy (MPS) as an advanced qualitative characterization method. This work focuses on the influence of concentration ratio and colloidal stability of nanoparticles on the overall remediation process. Herein, MPS enables the in situ real-time monitoring of the agglomeration events and illustrates that high colloidal stability of the SPIONs prevents the formation of large, destabilized agglomerates and thus their successful magnetic removal. Furthermore, it is shown that at high SPION concentrations, nanoparticle residuals are left in dispersion after collection of formed agglomerates, while at low concentrations nanoplastic leftovers are found. Colloidal stability and concentration-dependence of the agglomeration process are recognized as key aspects to focus on when developing future particle-based materials for nanoplastic remediation from water.
CRIS-Team WoS Importer:2022-06-17

Remediation of charged organic pollutants—binding motifs for highly efficient water cleaning with nanoparticles - Eigen, Andreas; Schmidt, Victoria; Sarcletti, Marco; Freygang, Selina; Hartmann-Bausewein, Andreas; Schneider, Vanessa; Zehetmeier, Anna; Mauritz, Vincent; Müller, Lukas; Gaß, Henrik; Rockmann, Linda; Crisp, Ryan; et al. (Nano Select, 2023)
Many charged organic molecules behave as persistent and hazardous pollutants with harmful effects on human health and ecosystems. They are widely distributed related to their charged molecular structure that provides water solubility. In order to track the fate and behavior of such pollutants, charged dyes with specific absorption in the visible spectra serve as convenient model compounds. We provide a platform of smart adsorbers that efficiently remediate positively and negatively charged dyes (crystal violet and Amaranth) from water. Metal oxide nanoparticles serve as a core with an intrinsically large surface area. The surface potential was tuned towards positive or negative by decorating the cores with self-assembled monolayers of dedicated long-chained phosphonic acid derivatives. Selective remediation of the dyes was obtained with corresponding oppositely charged core-shell nanoparticles. Mixed dye solution can be cleaned by a cascade approach or by applying both particle systems simultaneously. The removal efficiency was determined as a function of particle concentration via UV-spectroscopy. The results of remediation experiments at different pH values and using superparamagnetic iron oxide nanoparticle cores lead to a simple process with recycling capabilit

Tailorable Nanoparticles for Magnetic Water Cleaning of Polychlorinated Biphenyls - Müller, Lukas; Zehetmeier, Anna; Höfling, Anna; Gaß, Henrik; Voß, Johannes; Krappmann, Daniel; Rockmann, Linda; Harrer, Elias; Zahn, Dirk; Hirsch, Andreas; Halik, Marcus (Small Methods, 2025)
Anthropogenic persistent organic pollutants pose a pressing threat to the environment and human health. They can be found in water bodies all around the world at low but hazardous concentrations. Typical representatives of this contaminant class are polychlorinated biphenyls (PCBs). Here, nanoparticulate core-shell water cleaning agents are presented, which are able to remove PCBs of various chlorination degrees from water. The core consists of superparamagnetic iron oxide nanoparticles (SPIONs) providing a large surface area that can be tuned via self-assembled monolayers (SAMs) composed of phosphonic acid derivates. This shell binds the pollutants non-covalently enabling facile magnetic water remediation. By employing positively charged or hydrophobic SAMs different PCBs can be preferentially removed. Furthermore, these orthogonal functionalities can be integrated into one SPION system. By combining charged and hydrophobic phosphonic acid derivates in so-called binary SAMs the removal preference can be convoluted, which works just as well in real river water. The cost-efficient availability of the base materials for these tailorable nanoparticles is complemented with recyclability laying the foundation for a sustainable water cleaning proces
Keywords: persistent organic pollutants; polychlorinated biphenyls; self-assembled monolayers; superparamagnetic iron oxide nanoparticles; tailorable adsorption; water remediation

Tunable Composition of Mixed Self-Assembled Shell-by-Shell Structures on Nanoparticle Surfaces - Eigen, Andreas; Stiegler, Lisa; Gradl, Susanne; Schneider, Vanessa; Wedler, Vincent; Gaß, Henrik; Müller, Lukas; Sarcletti, Marco; Heinrich, Markus; Hirsch, Andreas; Halik, Marcus (Advanced Materials Interfaces, 2022)
The formation of mixed shell-by-shell (SbS) systems with tunable shell compositions is demonstrated by using molecular self-assembly driven by chemical recognition motifs. Aluminum oxide nanoparticles (AlOx-NPs) act as template surface for a self-assembled monolayer (SAM) of either partially fluorinated fluoroalkyl or alkyl chained phosphonic acid derivatives or defined stoichiometric mixtures of those. By providing an equimolar mixture of corresponding fluoroalkyl and alkyl-chained amphiphiles in water, the stoichiometry of underlaying mixed SAM on the NP-surface preferentially directs the composition of the secondary self-assembly. The composition of the shell-by-shell assemblies is studied by high performance liquid chromatography and fluorescence spectroscopy. The concept allows the formation of NP-templated vesicle-like bilayer structures, even consisting of orthogonal chain structures in tunable composition driven by chemical recognition and hydrophobic segregation.
Created from Fastlane, Scopus look-up
Keywords: hydro-; fluoro-; lipophilic/phobic; nanoparticles; self-assembly; shell-by-shell architectures; surface chemistry